Javno naročanje kot del politične modernizacije in evropeizacije v Sloveniji - Šoltes, Igor (Teorija in praksa, 2008)
A public procurement procedure is one of the non-authoritative procedures with the objective to establish the financial relation between the state and the market or the private sector in providing for the needs of the state and in implementing its function. The term state includes wide spectrum of the subjects that manage public funds and with its operations form the society and relationships in it. Public procurement needs to be understood in the context of the political modernization, since public procurement is a part of a process of denationalization of services that are necessary to provide for the general needs of the society. The area of public procurement is closely linked to the processs of approximation of the European law to the Member States.
Keywords: politična modernizacija; evropeizacija; javna naročila; država; state; Slovenia; Slovenija